Magicians Season 5 Disc 3 - Maeve, Stella; Appleman, Hale, 1986-; Gupta, Arjun, 1987-; Bishil, Summer, 1988-; Grossman, Lev.; Universal Pictures Home Entertainment (Firm) (Universal City, CA : Universal Pictures Home Entertainment, 2020)
A grad student at Brakebills College for Magical Pedagogy, has been fascinated by the magical fantasy world since he was young. But as he has gotten older, Quentin and his 20-something friends have discovered that the magical world they read about as children is not only real, but it poses dangers to humanity.
Purgatory -- Be the Hyman -- The balls -- Fillory and further.
Title from disc label.
Based on the best-selling novels by Lev Grossman.
Originally broadcast as single episodes of a television program in 2020.
Stella Maeve, Hale Appleman, Arjun Gupta, Summer Bishil.
Not rated.
DVD, region 1, NTSC; anamorphic wide screen (1.78:1); Dolby digital 5.1.
Keywords: Magic; Good and evil; Supernatural; Secret societies; College students; New York (State); Drama; Fantasy television programs; Fiction television programs; Horror television programs; Television programs; Video recordings for the hearing impaired